PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN VIDEO TERHADAP HASIL BELAJAR SISWA MATA PELAJARAN KBGT - Yayuk Sulistio Rini; Hanesman Hanesman (Universitas Negeri Padang, 2019)
This study aims to determine the effect of video-based learning media on class X student learning outcomes in Technical Drawing subjects. This research was conducted in class X TAVI and X TAV2 SMK Negeri 5 Padang. The research took place in April 2019. The research method used was a quasi-experimental design with posttest-only control design and purposive sampling technique. The instrument used was a multiple choice objective test. Data from test instruments were analyzed quantitatively. Based on data analysis, the value of thitung > ttabel which is 1.99>1.685, which means Ha is accepted. Then the use of video learning media has a positive influence on student learning outcomes. The average class of student learning outcomes is 80.1> Kontrol class is 74.9. There is an increase in the average value of the class of cement after treatment. Learning using video has an influence on the learning process with a percentage of 6.94% Keywords: video based learning media, engineering drawings, KBGT learning outcomes.